SEMIOTIC ANALYSIS OF THE LYRICS OF THE SONG "RUANG BARU" BY BARSENA BESTANDHI: A REPRESENTATION OF HOPE AND HEALING OF WOUNDS FROM ROLAND BARTHES' PERSPECTIVE - Dedi Satriawan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Music is not just entertainment, but a mass communication medium rich in signs and meanings. This study aims to analyze the denotative, connotative, and mythical meanings contained in the lyrics of Barsena Bestandhi's song "Ruang Baru" using Roland Barthes' semiotic analysis. This song, popular as the original soundtrack for the Indonesian version of the film My Annoying Brother, raises the themes of separation, acceptance, and the hope of reunion. The research method used is descriptive qualitative with an interpretive approach. The results show that: (1) Denotatively, the lyrics depict the cycle of nature (dry season, rain, rivers) as an analogy for the journey of life; (2) Connotatively, "Ruang Baru" represents a phase of post-traumatic emotional maturity, where individuals no longer view separation as an end, but rather a transition; (3) The myth constructed is the concept of "restorative destiny," where human suffering is validated as a temporary process towards eternal happiness.